ЎЗБЕКИСТОН ЖАНУБИДАГИ ИҚЛИМ ШАРОИТИДА ҚУЁШ ҲОВУЗИНИНГ ҲАРОРАТ РЕЖИМИНИ ЭКСПЕРИМЕНТАЛ ЎРГАНИШ - Узоков, Гулом; Элмуродов, Нуриддин; Давлонов, Хайрулла (Innovatsion texnologiyalar, 2022)
This article is devoted to the experimental study of the temperature regimes of the solar pond in the climatic conditions of the south of Uzbekistan. Research work in the experimental solar pond was carried out in September 2022. According to the research results, it is scientifically substantiated that the temperature of the lower layer of the pond increases by 56 oC at a concentration of 25% salt water in the solar pond, and the energy collection efficiency of the lower convective zone of the solar pond increases in parallel with the increase in solar radiation.